Who Uses the Patient Internet Portal? The PatientSite Experience - Weingart, Saul N. (American Medical Informatics Association, 2006)
Objective: Although the patient Internet portal is a potentially transformative technology, there is little scientific information about the demographic and clinical characteristics of portal enrollees and the features that they access. Design: We describe two pilot studies of a comprehensive Internet portal called PatientSite. These pilots include a prospective one-year cohort study of all patients who enrolled in April 2003 and a case-control study in 2004 of enrollees and nonenrollees at two hospital-based primary care practices. Measurements: The cohort study tracked patient enrollment and features in PatientSite that enrollees accessed, such as laboratory and radiology results, prescription renewals, appointment requests, managed care referrals, and clinical messaging. The case-control study used medical record review to compare the demographic and clinical characteristics of 100 randomly selected PatientSite enrollees and 100 nonenrollees. Results: PatientSite use grew steadily after its introduction. New enrollees logged in most frequently in the first month, but 26% to 77% of the cohort continued to access the portal at least monthly. They most often examined laboratory and radiology results and sent clinical messages to their providers. PatientSite enrollees were younger and more affluent and had fewer medical problems than nonenrollees. Conclusion: Expanding the use of patient portals will require an understanding of obstacles that prevent access for those who might benefit most from this technology.